2011
DOI: 10.1002/ajmg.a.33965
|View full text |Cite
|
Sign up to set email alerts
|

Multiple increased osteoclast functions in individuals with neurofibromatosis type 1

Abstract: Skeletal abnormalities including scoliosis, tibial dysplasia, sphenoid wing dysplasia, and decreased bone mineral density (BMD) are associated with neurofibromatosis type 1 (NF1). We report the cellular phenotype of NF1 human-derived osteoclasts and compare the in vitro findings with the clinical phenotype.Functional characteristics (e.g. osteoclast formation, migration, adhesion, resorptive capacity) and cellular mechanistic alterations (e.g. F-actin polymerization, MAPK phosphorylation, RhoGTPase activity) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…Moreover, experiments by others demonstrated that actin filament dynamics is affected by a reduced neurofibromin dose in human fibrosarcoma cell line via changes in the Rho-ROCK-LIMK2-Cofilin pathway [Ozawa et al, 2005]. The increased actin belt formation in human-derived cultured NF1 +/-osteoclasts is also a consequence of the hyperactivity RhoGTPase pathway [Stevenson et al, 2011]. These observations suggest that a NF1 haploinsufficiency might cause an altered organization and assembly of cytoskeletal proteins, which may affect cell mechanical properties of the cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, experiments by others demonstrated that actin filament dynamics is affected by a reduced neurofibromin dose in human fibrosarcoma cell line via changes in the Rho-ROCK-LIMK2-Cofilin pathway [Ozawa et al, 2005]. The increased actin belt formation in human-derived cultured NF1 +/-osteoclasts is also a consequence of the hyperactivity RhoGTPase pathway [Stevenson et al, 2011]. These observations suggest that a NF1 haploinsufficiency might cause an altered organization and assembly of cytoskeletal proteins, which may affect cell mechanical properties of the cells.…”
Section: Discussionmentioning
confidence: 98%
“…the production of melanin in melanocytes [Kaufmann et al, 1991;De Schepper et al, 2005], of osteopontin in osteoblasts [Li et al, 2009], of FGF-2, PDGF and midkine in Schwann cells [Mashour et al, 2001], or of collagen in fibroblasts [Yang et al, 2006]. Some NF1 +/-cells display more variable sizes and shapes than their NF1 +/+ counterparts, when they are cultured on surfaces with high stiffness such as Schwann cells [Rosenbaum et al, 2000], keratinocytes [Koivunen et al, 2000;Korkiamäki et al, 2002] or osteoclasts [Heervä et al, 2010;Stevenson et al, 2011]. Several findings demonstrate alterations in the cytoskeletal organization by NF1 haploinsufficiency.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The function of neurofibromin in synaptogenesis (9) and formation of barrel cortex (13) may partially explain these neurological symptoms. It is also known that neurofibromin regulates the functions of osteoclast (14,15) and skeletal muscle development (16). Although the Ras/MAPK pathway, the downstream signaling of neurofibromin, has been implicated in bone resorption (17), the detailed mechanism underlying the bony defects in patients with NF1 remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen bisphosphonates could theoretically have utility in NF1-related pseudarthrosis management because of the documented overactivity of NF1 osteoclasts, 12,13 and on the osteoclastogenic properties of BMP-2. Bisphosphonates act on the mevalonate pathway, the inhibition of which can reduce MAPK activation due to the lack of correct membrane localization of small GTPases.…”
Section: Pharmacological Therapies As An Adjunct To Surgical Treatmentmentioning
confidence: 99%